King Saul"s mysterious malady - Williams, Gillian P. (HTS teologiese studies, 2012)
This article investigates the ‘illness’ of King Saul (as narrated in the Old Testament). The ‘anti-Saul narrative’ states that ‘God’s spirit had left Saul’ and ‘an evil one had taken its place’ (1 Sm 16:14; also cf. e.g. of his behaviour in 1 Sm 19:24; 1 Sm 18:28−29). The latter years of Saul’s reign were marred by his pre-occupation with David’s growing popularity. He eventually became mentally unstable and suspected everyone of plotting against him. Saul’s battle against the Ammonites, as well as his last battle against the Philistines at Mount Gilboa, was fraught with difficulty. It is postulated that Saul experienced epileptic-like fits and assumedly suffered from some kind of ‘depression’ as a result of post-traumatic stress disorder (cf. 1 Sm 18:9; 1 Sm 18:28, 29; 1 Sm 19:24). This was possibly exacerbated by the enemy herem principle. Talmudic and other perspectives were also provided in the article where possible.